Sureśvara's vārtika on Śiśu and Mūrtāmūrta Brāhmaṇa - Jog, K. P.; Hino, Shoun (Motilal Banarsidass Publishers, 1996)
English translation with study of a supercommentary on Śaṅkarācārya's Bhāṣya on Br̥hadāraṇyakopaniṣad, Hindu philosophical classic.